(untitled) (Baghdad Science Journal, 2025)
Adult males of cucurbits fruit fly Dacus ciliatus (Loew) emerged from 7 days old pupae that were irradiated with 100 Gray , showed good competitiveness value when released with unirradiated males and females in ratios of 3 : 1: 1 and 5 :1 :1 (irradiated males: unirradiated males : unirradiated females) and high competitiveness value at ratios of 7 :1 :1 and 9 :1 :1 . While males emerged from 120 Gray irradiated pupae showed good competitiveness value at ratios of 7 :1 :1 and 9 :1 :1. The results of measuring the flight ability index of flies emerged from 7 days old irradiated pupae showed that irradiation with 80, 100 and 120 Gray by different doses of Gamma rays was significantly decreased at 200 Gray.